Risk factors for arteriovenous fistula thrombus development: a systematic review and meta-analysis - Yuhan Zhang; Jing Yi; Rongzhi Zhang; Yu Peng; Jianli Dong; Liyan Sha (Karger Publishers, 2022)
Background: Risk factors like femal sex, fistula location, hypertension, albumin, diabetes, age and other factors are related to arteriovenous fistula thrombus (AVFT), but the consistency and magnitude of their associations have not been confirmed by meta-analysis. Objectives：The purpose of this study was to provide a comprehensive and up-to-date synthesis of evidence on the association between potential risk factors and AVFT. Methods: In this systematic review and meta-analysis, PubMed, Embase, Cochrane Library, and Web of Science databases were searched for articles published up to April 20th, 2022, and cohort, cross-sectional, and case-control studies examining the association (odds ratio [OR]) between potential risk factors and AVFT were identified. The other inclusion criteria were sufficient data for analysis and non-overlapping datasets, excluding reviews, meta-analyse and articles with overlapping datasets. Extracted variables included first author, publication year, study type, sample size, percentage of women, vascular access type, risk or protective factors, and measure of association (adjusted estimates of effect of all risk factors). The study protocol is registered at PROSPERO (CRD42020201884) and followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Among the 27 identified studies, data from 24 cohort, 2 case-control and 1 cross-sectional study were included in this review. When compared to non-AVFT, our data showed that the significant risk factors were arteriovenous graft (pooled OR = 6.28, 95% CI = 1.79-22.02, p=0.004, I2=87%), age (pooled OR = 1.06, 95% CI = 1.00-1.13, p=0.05, I2=98%), female sex (pooled OR = 2.62, 95% CI = 2.56-2.69, p<0.00001, I2=0%), c-reactive protein (pooled OR = 1.18, 95% CI = 1.08-1.30, p=0.0005, I2=90%), fistula site (distal) (pooled OR = 3.64, 95% CI = 1.74-7.62, p=0.0006, I2=47%), hypertension (pooled OR = 1.21, 95% CI = 1.00-1.47, p=0.05, I2=46%), CD34+KDR+ cell (pooled OR = 1.85, 95% CI = 1.33-2.57, p=0.0002, I2=0%) and eprex use (pooled OR = 5.36, 95% CI = 1.82-15.77, p=0.002, I2=0%). Conclusions: The meta-analysis suggests that AVG, age, female sex, CRP level, fistula site (distal), hypertension, CD34+KDR+ cell and the use of eprex are independent risk factors for AVFT. Therefore, clinical medical staff should treat these risk factors carefully, identify them early and prevent them early to reduce the occurrence of AVFT.